Reputasi Perusahaan Memediasi Pengaruh Employer Branding Terhadap Niat Mahasiswa Generasi Z untuk Melamar Pekerjaan - Hapsara, Gregorius Purnawan Indra; Tri Hardjanti Nugrahaningsih (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to determine the impact of employer branding on job application rates, focusing on the role of corporate reputation as a mediator. The subjects of this study consisted of a sample of 131 Generation Z students in Semarang who were about to enter the workforce. Participants were recruited using purposive sampling. Data were collected using a questionnaire, and data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS version 3.2.9. The results show that employer branding has a significant impact on overall corporate reputation. The impact of corporate reputation on the intention to apply for a job is also seen in the results of the study. And the impact of employer branding on the intention to apply for a job on work-ready generation Z students in Semarang will be more influential when there is corporate reputation as a mediator. Based on this research, organisations or companies need to take into account the importance of forming a positive image, which serves as a marketing strategy for employer branding to attract the best/potential job applicants.